Roughness-Controlled Self-Assembly of Mannitol/LB Agar Microparticles by Polymorphic Transformation for Pulmonary Drug Delivery - Zhang, Fengying (2016)
Novel roughness-controlled mannitol/LB Agar microparticles were synthesized by polymorphic transformation and self-assembly method using hexane as the polymorphic transformation reagent and spray-dried mannitol/LB Agar microparticles as the starting material. As-prepared microparticles were characterized by Fourier transform infrared spectra (FTIR), X-ray diffraction spectra (XRD), differential scanning calorimetry (DSC), scanning electron microscopy (SEM), thermal gravimetric analysis (TGA), and Andersen Cascade Impactor (ACI). The XRD and DSC results indicate that after immersing spray-dried mannitol/LB Agar microparticles in hexane, β-mannitol was completely transformed to α-mannitol in 1 h, and all the δ-mannitol was transformed to α form after 14 days. SEM shows that during the transformation the nanobelts on the spray-dried mannitol/LB Agar microparticles become more dispersed and the contour of the individual nanobelts becomes more noticeable. Afterward, the nanobelts self-assemble to nanorods and result in rod-covered mannitol/LB Agar microparticles. FTIR indicates new hydrogen bonds were formed among mannitol, LB Agar, and hexane. SEM images coupled with image analysis software reveal that different surface morphology of the microparticles have different drug adhesion mechanisms. Comparison of ACI results and image analysis of SEM images shows that an increase in the particle surface roughness can increase the fine particle fractions (FPFs) using the rod-covered mannitol microparticles as drug carriers. Transformed microparticles show higher FPFs than commercially available lactose carriers. An FPF of 28.6 ± 2.4% was achieved by microparticles transformed from spray-dried microparticles using 2% mannitol(w/v)/LB Agar as feed solution. It is comparable to the highest FPF reported in the literature using lactose and spray-dried mannitol as carriers.